2017
DOI: 10.1016/j.bjid.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spread of an ongoing outbreak of Zika virus disease in pregnant women in a Mexican hospital

Abstract: In the first nine weeks of implementation of a Zika Virus Preparedness Plan in a Mexican Public Hospital, we cared for 221 pregnant women with any signal or symptom suggesting Zika virus infection and 99 (44.8%) patients were found to be positive for Zika virus. The median age of patients was 25.3 years (range 13-49). Symptoms in PCR-positive patients were rash (91.4%) followed by headache (53.1%), myalgia (46.9%), arthralgia (45.7%), pruritus (35.8%), retroocular pain (29.6%), conjunctivitis (21%), and fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Taste disturbances, pharyngitis, and other symptoms were rarely described. For ZIKV, fever, headache, chills, arthralgia, conjunctivitis, nausea, myalgia, pruritus, rash, retro-orbital pain, and abdominal pain have been previously reported by other working groups [5,6,39,40].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Taste disturbances, pharyngitis, and other symptoms were rarely described. For ZIKV, fever, headache, chills, arthralgia, conjunctivitis, nausea, myalgia, pruritus, rash, retro-orbital pain, and abdominal pain have been previously reported by other working groups [5,6,39,40].…”
Section: Discussionmentioning
confidence: 70%
“…Arbovirus is manifested as a wide variety of clinical symptoms in the host that can range from asymptomatic or oligosymptomatic infection to even death [1,2]. During the acute phases of arboviruses such as dengue fever (DENV), chikungunya (CHIKV), and zika (ZIKV), the clinical manifestations are similar [3][4][5][6][7]. This fact complicates correct identification.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial Aedes and Culex-borne arbovirus transmission is widely ignored by surveillance and vector control programs, even though healthcare-associated infections (HAI) are considered a serious threat to patient safety worldwide [35,36]. This is particularly troublesome, as pointed out by Garza-González et al (2017) [37], who reported a rapid ZIKV infection in pregnant women in a teaching hospital in Mexico. According to the WHO [38], the precise burden of HAI in low and middle-income countries remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic Zika infection is characterized by rash, fever, conjunctivitis, malaise, myalgia, arthralgia, edema, headache, and retro-ocular pain ( Brooks et al, 2017 ; Garza-González et al, 2017 ), which makes it difficult to differentiate clinically from dengue and chikungunya virus infections, which are both regionally endemic ( Braga et al, 2017 ; Colombo et al, 2017 ). Moreover, concurrent outbreaks and even co-infections may occur ( Braga et al, 2017 ; Mercado-Reyes et al, 2019 ), and the clinical presentation may vary geographically ( Braga et al, 2017 ; Brenciaglia et al, 2018 ; Silva et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%